Identifikasi Mangrove Berdasarkan Salinitas di Desa Sumber Jaya, Taman Wisata Alam (TWA) Pantai Panjang dan Pulau Baai Provinsi Bengkulu - Sudayu, Zayadi; Astuti, R.R. Sri; Fatimatuzzahra; Supriati, Rochmah; Riandini, Evelyne (Universitas Bengkulu, 2025)
Mangroves play an important ecological and economic role. TWA Pantai Panjang and Pulau Baai, specifically in Sumber Jaya Village, are directly adjacent to a river environment where seawater can enter during high tide. This seawater influence can affect the salinity of the waters, leading to varied responses from mangroves due to their differing tolerance ranges. The research aimed to identify mangrove species based on salinity conditions in Sumber Jaya Village, Kampung Melayu District, TWA Pantai Panjang, and Pulau Baai, Bengkulu Province. The research method used was descriptive explorative, with data collection at 3 stations using the Line Transect Plot method. The identification yielded 16 mangrove species from 9 families. Specifically, the Rhizophoraceae family included Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Bruguiera gymnorrhiza, and Bruguiera sexangular. The Avicenniaceae family was represented by Avicennia marina and Avicennia lanata. Other families included Combretaceae (Lumnitzera littorea and Terminalia catappa), Sonneratiaceae (Sonneratia alba and Sonneratia caseolaris), Acanthaceae (Acanthus ilicifolius), Asclepiadaceae (Calotropis gigantea), Apocynaceae (Cerbera manghas), Leguminosae (Derris trifoliata), and Malvaceae (Hibiscus tilaceus). The Rhizophoraceae family had the most species. Rhizophora apiculata, Rhizophora mucronata, and Rhizophora stylosa were found in a salinity range of 0 - 25 ‰, corresponding to freshwater to estuarine salinity types. Bruguiera gymnorrhiza and Bruguiera sexangula were found at salinities of 8-25 ‰, Avicennia marina and Avicennia lanata at salinities of 21-25 ‰, and Lumnitzera littorea at a salinity of 3 ‰.